The natural history of pediatric Sturge-Weber Syndrome: A multinational cross-sectional study - Disse, Sigrid Claudia; Küpper, Hanna; Bock, Annette; Korenke, Georg Christoph; Ramantani, Georgia; Weidner, Birgit; Preisel, Martin; Trollmann, Regina; Wiemer-Kruel, Adelheid; Brockmann, Knut; Schroeder, Simone; Meyer, Sascha (European Journal of Paediatric Neurology, 2025)
Background: Sturge-Weber Syndrome (SWS) is a capillary-venous malformation which includes the brain (leptomeningeal venous capillary malformation), the eye (choroidal angioma) and the skin (facial portwine birthmark, FPB). Structural epilepsy, glaucoma and FPBs pose therapeutic challenges. Considerable advances include improved neuroimaging, new antiseizure medication (ASM) and progress in epilepsy surgery. Yet, comprehensive data on epidemiology, clinical features, diagnostics, and treatment in contemporary pediatric SWS cohorts is scarce. Methods: We conducted a multinational cross-sectional observational study in Germany, Switzerland and Austria to identify potential patients and build up a comprehensive database containing anonymized patient data. The patients’ guardians and child neurologists filled in detailed questionnaires on histories, clinical features, diagnostic and therapeutic measures. Results: Forty-seven SWS patients from Germany, Switzerland or Austria participated in our survey (111 notifications, i.e. the participation rate was 43 %). Prevalence was 7.37/million in Germany, 4.60/million in Switzerland, 2.61/million in Austria. Severity of skin, eye and brain involvement varied highly. Forty-three patients (91 %) were diagnosed with epilepsy. Median age at first seizure was 6.5 months. Thirty-two percent of the cohort received ASM in monotherapy, fifty-three percent received combination therapy and thirteen percent received no ASM. Eight percent underwent epilepsy surgery. Conclusions: In this European pediatric SWS cohort from a well-established tertiary child neurologist network, the condition was commonly diagnosed within the first year of life. 40 % of the cohort were seizure-free at inclusion; only 8.5 % of the cohort underwent epilepsy surgery. Our findings are concordant with published data from U.S. registries and case series. While our results indicate diagnostic improvement as compared to published studies, epilepsy management in SWS remains a challenge.
CRIS-Team Scopus Importer:2025-02-28
Keywords: ESNEK; Observational study; Pediatric study; Phacomatosis; Sturge-Weber Syndrome